The various roles of TREM2 in cardiovascular disease - Wang, Shuai; Cao, Chenghui; Peng, Daoquan (Frontiers in Immunology, 2025)
Triggering receptor expressed on myeloid cells-2 (TREM2) is a transmembrane immune receptor that is expressed mainly on macrophages. As a pathology-induced immune signaling hub, TREM2 senses tissue damage and activates immune remodeling in response. Previous studies have predominantly focused on the TREM2 signaling pathway in Alzheimer’s disease, metabolic syndrome, and cancer. Recent research has indicated that TREM2 signaling is also activated in various cardiovascular diseases. In this review, we summarize the current understanding and the unanswered questions regarding the role of TREM2 signaling in mediating the metabolism and function of macrophages in atherosclerosis and various models of heart failure. In the context of atherosclerosis, TREM2 signaling promotes foam cell formation and is crucial for maintaining macrophage survival and plaque stability through efferocytosis and cholesterol efflux. Recent studies on myocardial infarction, sepsis-induced cardiomyopathy, and hypertensive heart failure also implicated the protective role of TREM2 signaling in cardiac macrophages through efferocytosis and paracrine functions. Additionally, we discuss the clinical significance of elevated soluble TREM2 (sTREM2) in cardiovascular disease and propose potential therapies targeting TREM2. The overall aim of this review is to highlight the various roles of TREM2 in cardiovascular diseases and to provide a framework for therapeutic strategies targeting TREM2.